(3GdGHJcGQ GdGSJQGJjLj aj UfGYI GdQjGVIs - (3ZGRj(B, (3eMeO YGUe eMeOs ((3YeGfs (3OGQ GdhaGb ddfTQ h GdJhRjYs, 2023)
"(3GdGHJcGQ GdGSJQGJjLj aj UfGYI GdQjGVI(B" (3gh cJGH jJfGhd LhGfH eJYOOI ef GdGHJcGQ aj eLGd GdQjGVI(B. (3jHOC GdcJGH HJbOje fXQI TGedI Ydi EOGQI GdGHJcGQ GdQjGVj, MjK jSJcTa GdCOhGJ hGdCSGdjH GdJj jecf ddefXeGJ GdQjGVjI GSJNOGegG dJYRjR KbGaI GdGHJcGQ hJTLjY GdCacGQ GdLOjOI(B. (3jfJbd GdcJGH HYO Pdc Edi efGbTI JbfjI GdQjGVI hGdGHJcGQ, MjK jSdW GdVhA Ydi GdJcfhdhLjGJ GdMOjKI GdJj jecf GSJNOGegG dJMSjf GdCOGA GdQjGVj, eKd GdJMdjdGJ GdQjGVjI, hGdhGbY GdGaJQGVj, hGdCLgRI GdbGHdI ddGQJOGA(B. (3aj GdaUd GdKGdK, jJYeb GdcJGH aj GdGHJcGQ GdGSJQGJjLj aj UfGYI GdQjGVI, MjK jfGbT cjajI JWhjQ GSJQGJjLjGJ GHJcGQjI dJMbjb ejRI JfGaSjI aj gPG GdeLGd SQjY GdJZjQ(B. (3jSJcTa GdcJGH CjkVG OhQ GdGHJcGQ aj JWhjQ GdefJLGJ hGdNOeGJ GdQjGVjI, hJMSjf JLQHI GdeTLYjf, hRjGOI GdEjQGOGJ(B. (3hCNjkQG, jfJgj GdcJGH HJbOje fXQI eSJbHdjI Ydi GdGJLGgGJ GdeJhbYI aj JcfhdhLjG GdQjGVI hGdGHJcGQ, eeG jhaQ ddbQGA QDjI hGVMI Mhd GdJWhQGJ GdeMJedI aj gPG GdeLGd(B. (3HGNJUGQ, gPG GdcJGH jbOe QDjI TGedI ddGHJcGQ aj UfGYI GdQjGVI, HOkAG ef GdCSGSjGJ hUhkdG Edi GdJWHjbGJ GdYedjI(B. (3hgh eUee deSGYOI GdbGOI hGdegfjjf aj UfGYI GdQjGVI Ydi age CgejI GdGHJcGQ hJWhjQ GSJQGJjLjGJ aYGdI dJYRjR Gdfeh hGdfLGM(B.s
Keywords: (3GdEOGQI GdQjGVjIs; (3GdJNWjW GdESJQGJjLjs; (3GdJQHjI GdQjGVjIs